Precedents of the compulsive use of a credit card: an analysis of university students' buying behavior (REGE Revista de Gestão, 2023)
Purpose – This study aims to identify the precedents of compulsively using a credit card, analyzing the influence of the following factors: power-prestige, anxiety, distrust, and materialism.Design/methodology/approach –Data collection was performed by the survey method, while the Structural Equation Modeling technique was used for data analysis, adopting the Confirmatory Factor Analysis and Path Analysis.Findings –The impact that anxiety has on compulsive use of credit cards was confirmed. Furthermore, the influence of materialism present in an individual on the compulsive use of a credit card was also proven.Research limitations/implications – As a limitation, the power-prestige construction did not obtain satisfactory AVE in the modeling. Other limitations can be pointed out, for example, it was a sample composed of university students and with geographic restrictions.Practical implications – This study highlights the importance of promoting public policies oriented towards the conscious use of credit cards. Interference in the approach of financial institutions aimed at attracting new clients in universities is also necessary.Social implications – This study can aggregate information about the buying behavior of university students, how the precedents affect credit card use behavior, and the harmful effects of compulsive use of credit cards.Originality/value – The originality of this study refers to a new approach to credit cards in analyzing their usage behavior, more specifically the compulsive use of credit cards.